Phytochemical analysis and green synthesis of silver nanoparticles using Centella asiatica leaf and stem extracts: An investigation of antibacterial activity - Kamana Sharma; Manisha Bhusal; Akash Budha Magar; Ishwor Pathak; Lok Kumar Shrestha; Khaga Raj Sharma (PLoS ONE, 2025)
Centella asiatica (L.) Urban is a traditionally revered plant possessing several therapeutic applications. This research evaluated the phytochemical and antibacterial properties of Centella asiatica. In addition, silver nanoparticles were synthesized using the stem and leaf aqueous extracts. The presence of alkaloids, flavonoids, glycosides, terpenoids, and phenolics in plant extracts indicates their high medicinal value. Methanolic leaf extract showed a higher phenolic and flavonoid content of 43.73 ± 0.33 mg GAE/g and 19.76 ± 1.12 mg QE/g, respectively. It also contained the most antioxidant activity with the lowest DPPH inhibitory concentration (IC50) of 49.31 ± 1.48 µg/mL. Plant extracts and synthesized nanoparticles were active against gram-positive and gram-negative bacteria. Methanolic leaf extract displayed an MIC of 27.5 and MBC of 55 mg/mL against S. aureus. Synthesized nanoparticles were characterized using different spectroscopic techniques. UV-visible spectra of nanoparticles contained distinct absorption peaks resulting from surface plasmon resonance at 405 and 408 nm. The nanoparticles showed face-centered cubic crystallinity in powder X-ray Diffraction analysis. Fourier Transfer Infrared spectra suggested the possible involvement of organic functional groups in nanoparticle synthesis. Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy analysis revealed the spherical shape with non-uniform size distribution. Mean particle sizes were 20 nm and 19 nm for leaf and stem extract synthesized nanoparticles, respectively. In conclusion, Centella asiatica is rich in important plant secondary metabolites and biological activities, and its aqueous extract synthesizes silver nanoparticles that show potential antibacterial activity.